Islamic Educational Leadership and Women’s Entrepreneurial Empowerment: A Pathway to Alleviating Extreme Poverty in Mojokerto, Indonesia - Rahma Sandhi Prahara; M. Umar Burhan; Asfi Manzilati; Marlina Ekawaty (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
Extreme poverty and limited economic access remain significant challenges for women in many developing regions, including Mojokerto, Indonesia. In response to these challenges, Islamic educational leadership has increasingly been positioned as a strategic approach to women’s economic empowerment through entrepreneurship. This study aims to examine the role of Islamic educational leadership in empowering women entrepreneurs through the 4P Entrepreneurial Incubation Program, a local government initiative implemented in collaboration with Islamic educational institutions. The program seeks to enhance women’s entrepreneurial capacity by integrating business skills, mentoring, and access to resources with Islamic values such as social justice, honesty, integrity, and community welfare. This study employs a qualitative research Design, using in-depth interviews with women participants, program administrators, and Islamic educational leaders, complemented by document analysis of program guidelines and reports. The findings indicate that Islamic educational leadership plays a transformative role in shaping entrepreneurial development by embedding moral and spiritual guidance within practical business training. This integration not only strengthens participants’ business competencies but also enhances ethical awareness, self-confidence, and resilience. Despite persistent challenges such as limited access to capital and socio-cultural constraints, incorporating Islamic values enables women to navigate obstacles and sustain their entrepreneurial activities. The study concludes that Islamic educational leadership is a critical factor in ensuring the effectiveness, sustainability, and ethical orientation of women-focused entrepreneurial incubation programs. The findings imply that faith-based leadership models can serve as a viable framework for poverty alleviation policies and for promoting women’s economic independence in similar socio-religious contexts.